Body Mass's Impact on Response to Fixed-Dose Vasopressin in Patients With Septic Shock. Issue 4 (October 2018) - Torbic, Heather; Sacha, Gretchen L.; Bauer, Seth R.; Lam, Simon W.
ABSTRACT: Introduction: The effect of patient weight and body mass index (BMI) on hemodynamic response to vasoactive medications is not fully understood. In titratable vasopressors, this effect is less likely a concern due to the ability to titrate dose to response; however, with the use of fixed-dose vasopressin, patient weight and BMI may impact response. Methods: This was a single-center, retrospective cohort of patients who received fixed-dose vasopressin for septic shock for at least 6 h with concomitant catecholamines in the medical, surgical, or neurosciences intensive care unit (ICU) at a tertiary care center. The association of weight- and BMI-adjusted vasopressin dose with change in catecholamine dose and change in mean arterial pressure (MAP) were evaluated using Spearman's correlation. Patients were further stratified by World Health Organization BMI categories to evaluate secondary outcomes. Results: There were 938 patients included with a median weight of 86.3 (70.6–106.6) kg and BMI of 29.5 (24.9–36.2) kg/m 2 . There was no correlation between weight-adjusted vasopressin dose and change in catecholamine dose ( r = −0.05, P = 0.13) or change in MAP ( r = 0.04, P = 0.31) 2 h after initiation of vasopressin. Similarly, no correlation was found when evaluating change in catecholamine dose or MAP at 6 and 12 h after vasopressin initiation (all P values >0.05). Comparable findings were observed when evaluating correlations between BMI-adjusted vasopressin dose with change in MAP and catecholamine dose at all time points (all P values >0.05). BMI groupings were balanced with 238 patients (25.4%) having a BMI less than 25, 254 patients (27.1%) having BMI 25 to 30, 182 patients (19.4%) having BMI 30 to 35, and 264 patients (28.1%) having BMI more than 35. The median duration of mechanical ventilation and ICU free days were 3.99 (1.50–5.07) and 0 (0–1.6) days, respectively, with no differences observed when stratified by BMI ( P = 0.59 and P = 0.83, respectively). In-hospital mortality was 64.8% and there was no difference among BMI groups ( P = 0.35). Conclusions: In this large cohort of septic shock patients, adjusting vasopressin dose for weight and BMI did not impact changes in catecholamine doses or MAP. Duration of mechanical ventilation, ICU free days, and mortality after vasopressin initiation were not affected by BMI.